Nonlinear forced vibration analysis of micro-rotating shaft–disk systems through a formulation based on the nonlocal strain gradient theory - Panahi, Ramin; Asghari, Mohsen; Borjalilou, Vahid (Archives of Civil and Mechanical Engineering, 2023)
The paper presents an upgraded size-dependent formulation for micro-rotating shaft–disks system to study their nonlinear forced vibration behavior. The novel formulation is based on the nonlocal strain gradient theory (NSGT). To achieve this goal, first of all, by incorporating the geometrical nonlinearity within the Rayleigh beam theory, the governing equations of the lateral motion of the system are derived by the Hamilton principle and then converted into a complex form. By defining some dimensionless parameters, the normalized form of the complex governing equation is also extracted. In the next step, the Galerkin method is implemented to establish an infinite set of ordinary differential equations (ODEs). Then, with the help of the method of multiple scales, the nonlinear ODE is solved to attain the vibrational amplitude of the system as well as its forward and backward natural frequencies. Lastly, an all-out parametric study is conducted to appraise the impact of some important factors like the nonlocal theory parameter, the strain gradient length scale parameter, the rotational speed, the amount of mass eccentricity and the internal damping coefficient on the motion amplitude and natural frequencies. The numerical outcomes illuminate well that depending on the relative value of two non-classical parameters of NSGT, this theory have the potential to reflect the hardening or softening attribute of small-scaled mechanical elements.